Advanced Therapies as a Social Right Limited by Budget Constraints: Reflections Between Constitutional Law and Bioethics (BioLaw Journal - Rivista di BioDiritto, 2026)
This contribution analyzes the legal and bioethical challenges posed by advanced therapy medicinal products (ATMPs), technologies with high potential but significant cost. The article explores the tension between the right to health (Art. 32 of the Italian Constitution) and economic sustainability (Art. 81), assessing whether access to therapeutic innovation can be considered a constitutionally guaranteed right. It also introduces bioethical reflections on resource allocation in conditions of scarcity, questioning the legitimacy of exclusions based on cost. The aim is to clarify the enforceability boundaries of access to ATMPs as a social right and the balancing mechanisms within the public health system.
Keywords: right to health; advanced therapies; economic sustainability; bioethics; Constitutional balancing